FACTORS INFLUENCING THE SUCCESS OF MSMES IN KENDARI: A QUALITATIVE PERSPECTIVE - Fahlevi, Anugrah Ryandra; Mokodompit, Eliyanti Agus (Penelitian dan Pengembangan Ilmu, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia play a significant role in the national economy; however, their success remains limited, especially in Kendari. Despite their large potential for growth, challenges such as limited access to financing, low financial management understanding, and underutilization of digital technology hinder their competitiveness. This study aims to identify factors affecting the success of MSMEs in Kendari and address the knowledge gap related to the challenges faced by business owners in the region. The study employed a qualitative approach, conducting in-depth interviews with five informants directly involved in the MSME ecosystem in Kendari, including business owners, government representatives, microfinance institution staff, academics, and MSME association leaders. The findings show that product quality, technology utilization, access to capital, and the role of social networks and government support are key factors in supporting the success of MSMEs in Kendari. The implications of this research emphasize the need to strengthen MSMEs' capacities in financial management and digital marketing and to improve coordination between the government, financial institutions, and associations to address the challenges faced by MSME owners.